Magnetospinography visualizes electrophysiological activity in the cervical spinal cord - Satoshi Sumiya (Nature Portfolio, 2017)
Abstract Diagnosis of nervous system disease is greatly aided by functional assessments and imaging techniques that localize neural activity abnormalities. Electrophysiological methods are helpful but often insufficient to locate neural lesions precisely. One proposed noninvasive alternative is magnetoneurography (MNG); we have developed MNG of the spinal cord (magnetospinography, MSG). Using a 120-channel superconducting quantum interference device biomagnetometer system in a magnetically shielded room, cervical spinal cord evoked magnetic fields (SCEFs) were recorded after stimulation of the lower thoracic cord in healthy subjects and a patient with cervical spondylotic myelopathy and after median nerve stimulation in healthy subjects. Electrophysiological activities in the spinal cord were reconstructed from SCEFs and visualized by a spatial filter, a recursive null-steering beamformer. Here, we show for the first time that MSG with high spatial and temporal resolution can be used to map electrophysiological activities in the cervical spinal cord and spinal nerve.